Enforceability of Foreign Language Contracts in Indonesia: A Legal Analysis of Language Law in Cross-Border Business Agreements - Lintang Lasmita Sari; Fabrian Iman Laksmono Simorangkir; Karlsen Adiyasa Bachtiar; Novena Kristina Sari; Reinhart Christian (Jurnal Ar Ro'is Mandalika (Armada), 2025)
This study explores the enforceability of foreign language contracts within the Indonesian legal system, focusing on the implications of Law No. 24 of 2009 and its implementing regulation, Presidential Decree No. 63 of 2019. These legal instruments mandate the use of Bahasa Indonesia in agreements involving Indonesian parties, including cross-border business transactions. Employing a qualitative, normative legal research methodology grounded in literature review (library research), this article examines statutory provisions, judicial decisions, and scholarly commentary to assess the consistency and clarity of legal enforcement. The study reveals significant inconsistencies in judicial interpretation and application of the language law—rulings have varied from nullifying contracts to accepting foreign language agreements, often dependent on interpretations of legal formality and good faith. The recent issuance of Supreme Court Circular Letter No. 3 of 2023 signals a shift toward more flexible enforcement, emphasizing intent and fairness over strict linguistic formalism. This inconsistency, however, generates legal uncertainty, increases transaction costs, and creates risks for opportunistic contract annulment. The study also compares Indonesia’s regulatory stance with Malaysia’s more permissive approach, which prioritizes contractual intent over language requirements. It argues that Indonesia must reform its legal framework to enhance certainty and investment attractiveness without undermining national identity. This reform includes clearer legal guidance and harmonization of judicial decisions to strike a balance between statutory compliance and international commercial practice.